2011
DOI: 10.1139/w11-099
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacteriophages with a lytic effect on various Salmonella serotypes and Escherichia coli O157:H7

Abstract: Four phages isolated from cattle and poultry feces were analyzed for their ability to lyse Salmonella serotypes and Escherichia coli O157:H7. The phage one-step growth curves, morphology, and genetic characteristics were determined. All phages showed a lytic effect on various Salmonella serotypes and E. coli O157:H7, which lysed at least 70% of the 234 strains tested. The phages had latent periods ranging from 10 to 15 min and generation times of 30 to 45 min, while burst size fluctuated between 154 and 426 PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
2
29
0
2
Order By: Relevance
“…While some previous studies have reported isolation of Salmonella phages from fecal samples collected from multiple hosts (i.e., humans, swine, and cattle), these previous studies have found lower frequency of Salmonella phage isolation from bovine fecal samples (i.e., 0–18%) (López-Cuevas et al, 2011; O’Flynn et al, 2006) as compared to a frequency of phage isolation of up to 81% from swine and poultry fecal samples (Andreatti Filho et al, 2007; Callaway et al, 2011; Hooton et al, 2011a; Wang et al, 2010). While these previous studies have used individual fecal samples, our study here used samples that represent natural pools of feces from animals on a given farm.…”
Section: Discussionmentioning
confidence: 86%
“…While some previous studies have reported isolation of Salmonella phages from fecal samples collected from multiple hosts (i.e., humans, swine, and cattle), these previous studies have found lower frequency of Salmonella phage isolation from bovine fecal samples (i.e., 0–18%) (López-Cuevas et al, 2011; O’Flynn et al, 2006) as compared to a frequency of phage isolation of up to 81% from swine and poultry fecal samples (Andreatti Filho et al, 2007; Callaway et al, 2011; Hooton et al, 2011a; Wang et al, 2010). While these previous studies have used individual fecal samples, our study here used samples that represent natural pools of feces from animals on a given farm.…”
Section: Discussionmentioning
confidence: 86%
“…Before the titration, the second set of samples was treated with 1% chloroform to artificially lyse the cell so the appearance of first infective phage particles can be accurately measure to determine the eclipse time [31]. The titer of samples were tested using the double-layer agar plate method [32].…”
Section: Determination Of Phage Adsorption Rate and One-step Growthmentioning
confidence: 99%
“…carotovorum strains were isolated from various host plants and locations in Korea [28]. The host range of bacteriophage PP1 was assessed using spot tests as published previously with minor modifications [23]. Each bacterial strain was cultured overnight with agitation, and 200 µl aliquots were mixed with 0.4% soft agar containing 10 mM MgSO 4 .…”
Section: Host Range Determinationmentioning
confidence: 99%